Carlos García Gual, Introducción a la mitología griega, Madrid, Alianza Editorial, 1992, 292 pp. ISBN 84-206-0580-8 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Carlos García Gual, Introducción a la mitología griega, Madrid, Alianza Editorial, 1992, 292 pp. ISBN 84-206-0580-8